Praenotio, Prisca Haeresis, and Astrology: Gianfrancesco Pico della Mirandola between Savonarola and Giovanni Pico - Akopyan, Ovanes (Renaissance and Reformation / Renaissance et Réforme, 2019)
This article considers the place of Gianfrancesco Pico della Mirandola’s ideas within the astrological debates that arose in Renaissance Italy after the publication of the Disputationes adversus astrologiam divinatricem by Giovanni Pico della Mirandola, Gianfrancesco Pico’s famous uncle. Published posthumously in 1496, the Disputationes incited a rigorous discussion of the status of astrology in various intellectual circles in Renaissance Italy. Gianfrancesco Pico was the editor of his uncle Giovanni Pico’s Opera, and the younger Pico was also known as one of Girolamo Savonarola’s most ardent followers. This article will focus on Gianfrancesco’s two main anti-astrological treatises, the De rerum praenotione and the Quaestio de falsitate astrologiae. Gianfrancesco’s writings reveal his own elaborate ideological agenda and the ways in which he used, in a controversial manner, both his uncle’s and Savonarola’s arguments in consequent philosophical and astrological discussions.